A CFD Study of Moist Air Conditioning in Classroom 4104-4105 FTMD ITB - Harun Al Rizki, Muhammad
Every classroom should have a good grade and quality to make sure the learning process runs optimally. One of the factor that influences the grade and quality of the learning process is the condition of the room. Temperature and humidity are some parameters that determines whether a room would be suitable to be occupied. On a preceding research, a simulation of classroom 4104-4105 have been done using dry air to analyze the condition and the comfort parameter of that classroom. On this undergraduate final project, classroom 4104-4105 simulations has been done using moist air. The simulation condition variates the number of people occupying the classroom between 51 and 94 and the door or window are variated in open or closed condition.The purpose of this undergraduate final project is to compare the result of the simulation using dry air with the simulation using moist air along with effect of humidity. Besides that, the comfort criteria have been analyzed based on ASHRAE Standard 55 and SNI to determine the suitable condition for learning process. Based on the simulation result, there are differences between the simulation using dry air and moist air. On the simulation using moist air, the final room temperature is higher, the simulation duration is longer, and the slope of the temperature drop graph declines more steeply than simulation using dry air. However, during the simulation with 94 people with enviromental conditions in September 2015, the final room temperature is lower than the simulation with 94 people with environmental conditions in September 2013. This low temperature phenomenon is caused by the high number of RH in the moist air in the room. Comfort conditions or thermal comfort is evaluated by specifying 6 points in classroom 41044105 for each simulation. The results shows that the comfort conditions is achieved at point